Constructing a patient-centred strategy to promote adherence to anti-diabetic medication: a mixed methods study - Abdullah, Nor Fadhilah; Lee, Khuan; Sowtali, Siti Noorkhairina; Juni, Muhamad Hanafiah; Anthony Abdullah, Muhammad Mikhail Joseph; Abdullah, Steven Eric Krauss @ Abdul Lateef; Mat Yusoff, Rozainah (2017)
Adherence to the medication and diabetes self-management are important in ensuring the successfulness of diabetes management. However, previous literature have reported on unsatisfactory rate of non-adherence among Type 2 diabetes patients. Quantitative studies on adherence may fail to understand the reason of non-adherence from the patients' perspective. Thus, a mixed method approach could be a better option to fill this gap. The aim of this study is to measure non-adherence cases among Type-2 diabetes patients and to explore the factors of non-adherence among non-adherence patients. A mixed-method sequential explanatory study will be applied. In the first quantitative phase, an adopted medication adherence questionnaire (MCQ) comprising seven questions will be used to assess the non-adherence rate. The score will be categorized into adherence and non-adherence patients. By using multistage sampling, two public hospitals were chosen for this study. The calculated sample size is 461. Patients will be selected from the weekly scheduled name list by using systematic random sampling. Data will be analysed using SPSS 22. Univariate analysis will be used to describe patients' characteristics. Bivariate and multivariate will be used to determine the comparison and association of variables with adherence. In the second qualitative phase, the respondents will be purposely chosen from the first phase of non-adherence patients. Semi-structured interviews will be conducted to explore the factors influencing patients' non-adherence. Theoretical sampling will be used to collect data until data saturation has been reached. Data will be analysed using constant comparative analysis with the help of NVivo 11 software to manage the data. Patient-centered strategies then will be formulated from the qualitative findings.